2020
DOI: 10.1002/adhm.202001489
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Therapy Directed by Three‐Photon Active Rigid Plane Organic Photosensitizer

Abstract: Multi‐photon photosensitizers (PSs) could significantly improve the efficacy of photodynamic therapy due to the long‐wavelength favorability for deeper tissue penetration and lower biological damage. However, most studies are limited to single‐photon or two‐photon PSs at a relatively short‐wave excitation window. To overcome this barrier, we rationally design a series of rigid plane compounds with efficient reactive oxygen species (ROS) production in vitro under laser irradiation. Furthermore, the studies show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 39 publications
0
8
0
2
Order By: Relevance
“…Additionally, multi‐photon PDT is associated with a higher spatial and temporal resolution in comparison to a one‐photon event [52] . While the majority of the published literature is focused on two‐photon PDT, [53] some studies have also reported on the use of three‐photon PDT [54] . Despite recent improvements in the development of multi‐photon excited light sources and PSs with an enhanced two‐photon absorption, no compound has advanced into clinical trials yet.…”
Section: Future Perspectives and Challengesmentioning
confidence: 99%
“…Additionally, multi‐photon PDT is associated with a higher spatial and temporal resolution in comparison to a one‐photon event [52] . While the majority of the published literature is focused on two‐photon PDT, [53] some studies have also reported on the use of three‐photon PDT [54] . Despite recent improvements in the development of multi‐photon excited light sources and PSs with an enhanced two‐photon absorption, no compound has advanced into clinical trials yet.…”
Section: Future Perspectives and Challengesmentioning
confidence: 99%
“…Although the increase in the degree of the 3PA cross section of ZA-Mex is minimal compared to ZA-Hex , the value in the aggregate state (4.98 × 10 –82 cm 6 s 2 per photon 2 ) has a 7.51-fold increase compared to the solution state (0.66 × 10 –82 cm 6 s 2 per photon 2 ) (Figure S19). ZA does not possess three-photon AIE emission behavior, and hence its absorption cross section has the value of 0 (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…25-fold increase compared to ZA-Mex in AIE conditions. The results are consistent with the hydrophobic interaction and electrostatic interaction in the molecules with long alkyl chains.…”
mentioning
confidence: 84%
“…[52] Während sich der Großteil der verçffentlichten Literatur auf die Zwei-Photonen-PDT konzentriert, [53] wurde in einigen Studien auch über die Verwendung der Drei-Photonen-PDT berichtet. [54] Tr otz jüngster Verbesserungen bei der Entwicklung von Lichtquellen fürM ulti-Photonen-Anregungen und PS mit einer verbesserten Zwei-Photonen-Absorption wurde bisher noch keine Verbindung in klinischen Studien untersucht. Interaktion einer tumoraffinen funktionellen Gruppen genutzt, wie sie beispielsweise in Antikçrpern, [55] Oligonukleotiden, [56] Oligosacchariden, [57] Vitaminen, [58] Signalpeptiden [59] oder Proteinen [60] zu finden ist.…”
Section: Multi-photonen-pdt -Tiefes Eindringen Des Lichts Ins Gewebe Sowie Hohe Räumliche Und Zeitliche Auflçsung Der Lichtbestrahlungunclassified
“…Darüber hinaus ist die Multi‐Photonen‐PDT im Vergleich zur Ein‐Photonen‐PDT mit einer höheren räumlichen und zeitlichen Auflösung verbunden [52] . Während sich der Großteil der veröffentlichten Literatur auf die Zwei‐Photonen‐PDT konzentriert, [53] wurde in einigen Studien auch über die Verwendung der Drei‐Photonen‐PDT berichtet [54] . Trotz jüngster Verbesserungen bei der Entwicklung von Lichtquellen für Multi‐Photonen‐Anregungen und PS mit einer verbesserten Zwei‐Photonen‐Absorption wurde bisher noch keine Verbindung in klinischen Studien untersucht.…”
Section: Zukunftsperspektiven Und Herausforderungenunclassified